2014
DOI: 10.1007/s11430-014-4960-y
|View full text |Cite
|
Sign up to set email alerts
|

A case study of the role of climate, humans, and ecological setting in Holocene fire history of northwestern Europe

Abstract: We present the major results from studies of fire history over the last 11000 years (Holocene) in southern Sweden, on the basis of palaeoecological analyses of peat sequences from three small peat bogs. The main objective is to emphasize the value of multiple, continuous sedimentary records of macroscopic charcoal (macro-C) for the reconstruction of local to regional past changes in fire regimes, the importance of multi-proxy studies, and the advantage of model-based estimates of plant cover from pollen data t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 71 publications
2
4
0
Order By: Relevance
“…11,200 and 9600 cal BP, was attested at the base of a levee, associated with high frequencies of pine pollen and microcharcoal. Although the link with the 10.3 ka event is less evident at Kerkhove, both sites are important as they demonstrate the occurrence of repeated wildfires during the (late) preboreal and early Boreal, when the landscape was dominated by coniferous forests, which is consistent with observations elsewhere in northern Europe [64]. These fires definitely must have impacted the human resources, but it is currently difficult to determine the precise extent.…”
Section: Discussionsupporting
confidence: 70%
“…11,200 and 9600 cal BP, was attested at the base of a levee, associated with high frequencies of pine pollen and microcharcoal. Although the link with the 10.3 ka event is less evident at Kerkhove, both sites are important as they demonstrate the occurrence of repeated wildfires during the (late) preboreal and early Boreal, when the landscape was dominated by coniferous forests, which is consistent with observations elsewhere in northern Europe [64]. These fires definitely must have impacted the human resources, but it is currently difficult to determine the precise extent.…”
Section: Discussionsupporting
confidence: 70%
“…In the last glacial, local fires commonly occurred in the Qinling region (Figure 4a) and biofuels in this interval were mostly supplied by woody plants (Figure 4f), corresponding to a high percentage of conifers (Figure 4g). Some studies have shown that boreal conifer forests such as Pinus are highly combustible (e.g., Cui et al, 2013Cui et al, , 2015. In our study, fire peak occurred during 21.6-21 cal ka BP, accompanied by a high abundance of woody plants (mainly conifers) and relative high temperatures (Figures 4b and 4c).…”
Section: Climate and Vegetation Influenced The Fire Activitysupporting
confidence: 54%
“…Furthermore, not only in China but also on other continents all reported this phenomenon that anthropogenic land‐use played a dominant tole in the increase in fire activity during the late Holocene (Cui et al . 2015; Schüpbach et al . 2015; Xu et al .…”
Section: Discussionmentioning
confidence: 99%